Japan: Moderner Hafen-, Industrie- und Infrastrukturausbau durch Neulandgewinnung an der Küste: Eine geographisch-politische Analyse des Struktur- und Landschaftswandels, der Umwelt- und Raumordnungsprobleme und der Prozeßregler - Flüchter, Winfried (ERDKUNDE, 1984)
The remarkable success of the Japanese economy during the last 30 years would have been impossible without the expansion of her harbours and harbour-related industries; the modern land, coast and urban development would be inconceivable without coastal reclamation. Meanwhile approximately 900 km2 umetate-chi (literally filled-up areas) have been reclaimed by the filling-up of land. The very beginning of this study describes the distribution of those umetate-chi in Japan and analyses the reasons for their construction. Special emphasis is given firstly to the functions and spatial structures of the filled-up areas, of which approximately 75% are used by harbour and raw material-based industries (oil refineries, petrochemical complexes, integrated steel works, thermal-electric power and gas stations, liquid natural gas and crude oil terminals, aluminium and food industry plants, storage bases, shipyards, and to a certain extent automobile factories etc.), about 7% by public trade harbours (e.g. container terminals), and the remaining 15-20% for urban and metropolitan regional infrastructures (rubbish incineration and waste-water treatment plants, industrial estates of relocated small and middle-sized enterprises, new airports, train lines, highways, leisure facilities, housing complexes, new water front areas with urban and marine parks etc.). Secondly, the impacts of the umetate land reclamation activities are discussed and assessed: the effects on fishery, coastal landscape, environmental problems, regional development and overdevelopment. Thirdly, the main political and socio-economic powers as decisive determinants of the land reclamation and coastal development are analyzed, whereby special attention is given to the essence and role of the state in Japan, particularly to the bureaucratization of politics.